PWE-161 Platelet activation in acute upper gastrointestinal bleeding. (28th May 2012) - Disney, B R; Watson, R; Blann, A; Lip, G; Tselepis, C; Anderson, M
Abstract : Introduction: Acute upper gastrointestinal bleeding (AUGIB) is a common reason for medical admissions and is associated with significant morbidity and mortality. Studies have previously noted an excess of cardiovascular events in patients who have suffered from AUGIB. Patients who have aspirin withheld for 8 weeks following admission with AUGIB have significantly higher rates of CVS events. The aim of the study was to assess the level of platelet activation, and platelet reactivity, in patients presenting with AUGIB. Methods: Patients admitted to Sandwell and West Birmingham Hospitals NHS Trust with AUGIB were recruited. Dyspeptic patients attending for diagnostic OGD were used as controls. To assess platelet activation citrated whole blood was incubated at room temperature with monoclonal mouse antibodies against constitutively expressed platelet marker CD42a-PerCP, and markers of platelet activation PAC1-FITC, and CD62P-APC. Negative controls were run in parallel. Incubation was terminated after 15 min. Platelet reactivity to an agonist, in this case ADP, was assessed by stimulating blood with ADP for 2 min prior to incubation with antibodies as described above. Samples were analysed using a FACSCalibur flow cytometer. Platelets were identified on the basis of their forward and side scatter properties and the presence of the CD42a platelet-specific marker. CD62P and PAC1 expression were measured by the percentage of platelets expressing these markers. Statistical significance of mean platelet activation was determined by the t-test. The Mann–Whitney U test was utilised for non-normally distributed data. Statistical analysis was performed using SPSS V.18.0 software. Results: A total of 31 patients with AUGIB and 25 controls were recruited. The groups were age and gender matched. The mean age of the AUGIB group is 66.4±18.2 years, and the control group 62.8±6.1 years. There was a significant differences in the level of CD62P positivity between the study groups (18.4±5.8% in AUGIB group and 13.9±3.7% in the control group, p=0.001) and in those staining positive for both CD62P and PAC1 (1.9±1.45% in AUGIB group and 1.2±1.0% in the control group, p=0.027). No differences were seen in PAC1 positivity between the groups (7.1±5.2 vs 5.1±4.2, p=0.127). No differences were seen in the response of platelets to ADP between the study and control groups. Conclusion: Patients presenting with AUGIB have higher levels of platelet activation when compared to controls. Platelet reactivity to ADP was similar between the two groups. In patients with high cardiovascular risk profiles early re-introduction of aspirin or other anti-platelet agents should be considered. Competing interests: None declared.